2015
DOI: 10.1016/j.cmi.2015.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology and burden of infection in patients with diabetes mellitus and peripheral vascular disease: focus on skin and soft-tissue infections

Abstract: Diabetes mellitus affects 284 million adults worldwide and is increasing in prevalence. Accelerated atherosclerosis in patients with diabetes mellitus contributes an increased risk of developing cardiovascular diseases including peripheral vascular disease (PVD). Immune dysfunction, diabetic neuropathy and poor circulation in patients with diabetes mellitus, especially those with PVD, place these patients at high risk for many types of typical and atypical infections. Complicated skin and soft-tissue infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
118
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(130 citation statements)
references
References 41 publications
5
118
0
7
Order By: Relevance
“…In addition, 152 DE genes in the skin (FDR < 0.2), which are also expressed in the muscle, showed a consistent T2DM-associated expression changes between the muscle and skin (Supplementary Figure 1). These results indicated the burden of infection in both human skin and muscle of T2DM, and are consistent with high rates of skin and soft-tissue infections observed in patients with type 2 diabetes [21]. …”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In addition, 152 DE genes in the skin (FDR < 0.2), which are also expressed in the muscle, showed a consistent T2DM-associated expression changes between the muscle and skin (Supplementary Figure 1). These results indicated the burden of infection in both human skin and muscle of T2DM, and are consistent with high rates of skin and soft-tissue infections observed in patients with type 2 diabetes [21]. …”
Section: Discussionsupporting
confidence: 79%
“…A number of studies have shown that patients with T2DM are associated with a higher risk of infectious diseases [2124]. About fifty percent of the diabetic patients involved in Shah's study had at least one hospitalization or physician claim for infection in each cohort year [23].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of both diabetes and HIV have been shown to lead to infectious complication. (Dryden et al, 2015; Knapp, 2013). It is, however, unclear why black race led to an increase in infectious complications.…”
Section: Discussionmentioning
confidence: 99%
“…En ellos, las soluciones de contigüidad con la consiguiente pérdida de la barrera cutánea permiten la entrada fácil de bacterias patógenas. Además, está demostrado que la DM y la EVP aumentan el riesgo de colonización por SARM en pacientes hospitalizados 11 . En el caso de nuestra paciente, si bien no contaba con los factores de riesgo descritos para el desarrollo de EG, presentaba otras co-morbilidades que favorecen el desarrollo de infecciones cutáneas complicadas: como DM mal controlada, EVP y ERC.…”
Section: Discussionunclassified